Camilo Torres Restrepo: Political struggle, Sociology and Praxis - Lucia Picarella (Culture e Studi del Sociale)
The aim of the present article is the study of the thought of Camilo Torres Restrepo through the consideration of the variables that have contributed to their development, in order to emphasize the extraordinary inheritance and validity of the camilismo. Following this line, we will proceed through the analysis of specific texts that will allow us to understand his reflection in religious, political, and social terms, in a combination that becomes praxis  and that takes concrete form in the strong criticism of the ecclesiastical hierarchy and left-wing forces, in his pioneering role in Liberation Theology and forerunner of the social problems that have characterized the Colombian context, in the importance of education and the founding of the first Sociology Faculty in Latin America, in the continuous appeal to politics unity and the entry into the rows of the guerilla.